Lexical and Symbolic Meanings of Dish Names in Mandailing Cuisine: An Ecolinguistic Study - Alvy Mawaddah; Laraiba Nasution; Abdul Gapur (Celt: A Journal of Culture, English Language Teaching and Literature, 2026)
Using an ecolinguistic approach, specifically the ecolexicon model, this study examines the lexical and symbolic meanings associated with naming traditional Mandailing dishes. However, few studies have explored the profound connection between this culinary lexicon and the broader environmental and cosmological worldview of the Mandailing people. The method is qualitative and uses linguistic ethnography and Spradley’s analysis. The data were collected through in-depth interviews, participatory observation, and a review of the literature on various dishes, including Sambal Tuktuk, Alame, and Gule Bulung Gadung. The results show that the Mandailing culinary lexicon not only includes information about ingredients and their preparation, but it also reflects social values such as mutual assistance, spirituality, environmental adaptation, and local cosmology. Dish names serve as a way to demonstrate that people and nature are in harmony with each other and to pass on cultural values. This study demonstrates the importance of preserving traditional dishes as part of a linguistic ecology that protects valuable local knowledge. These results offer a means to analyze other ethnic cuisines and help strengthen cultural identity by documenting traditional vocabulary.